Review: Phytochemical of Some Plants with Anticoagulant - Sitiawani, Meisy; Azizah, Zikra; Asra, Ridho; Chandra, Boy (Asian Journal of Pharmaceutical Research and Development, 2022)
Background: Anticoagulants are drugs used to treat hypertension and cardiovascular disease.This review article aims to discuss several types of natural plants with anticoagulant activity. Materials and Methods: The method used is the study of relevant literature(national and international journals) which is accessed through online sites such as Google Scholar, Research Gate, Science Direct, Springer Link, and NCBI, published in the last 10 years (2011-2021) with the keyword “herbal plant” or “medicinal plant” and “anticoagulant” and “cardiovascular”. Results: Based on in vitro and in vivo tests, some plants such as Allium sativum L., Averrhoa bilimbi, Persea americana Mill., Tridax procumbens L., Carica papaya L., Rhizophora sp, Syzygiumcumini L., Piper batle L., Erigeron canadensis L., Ainsliaea fragrans, Averrhoa bilimbi, Carica papaya L., are types of plants with anticoagulant activity. Conclusion: Herb can be used as alternative sources of new anticoagulant agents cause of their biological activity. The use of medicinal plants with therapeutic effects and minimal side effects can be the best choice for the prevention and treatment of various diseases including cardiovascular disorders.